Pemanfaatan Perasan Kulit Nanas (Ananas Comosus L.) dalam Formulasi Sediaan Hand Sanitizer untuk Menghambat Pertumbuhan Escherichia Coli - Dina Ayu Puspita Rinni; Egga Azahra Nabilla; Ella Defita Rizky; Haz Ha Putra (STIKES Columbia Asia Medan, 2025)
The low level of public awareness regarding hand hygiene has become a contributing factor to the spread of infectious diseases transmitted through contact. This condition has sparked innovation in the development of hand sanitizer products made from natural ingredients, which are not only effective in killing germs but also safe and environmentally friendly. One promising natural ingredient is pineapple peel (Ananas comosus L.), which is generally considered organic waste. Pineapple peel contains bioactive compounds such as flavonoids, tannins, and the enzyme bromelain, all of which possess antibacterial properties. This study aims to evaluate the antibacterial effectiveness of pineapple peel extract against the growth of Escherichia coli and assess its feasibility as an active ingredient in spray hand sanitizer formulations. The research method involved preparing spray hand sanitizer with varying concentrations of pineapple peel extract: 50%, 60%, 70%, 80%, and 90%. Antibacterial activity was tested using the disk diffusion method to measure the inhibition zone against E. coli. Additional evaluations included physical quality tests such as pH, spreadability, homogeneity, organoleptic properties, skin irritation test, storage stability, and consumer preference. The results showed that the 90% concentration formulation had the highest antibacterial effectiveness, with an inhibition zone of 22 mm. This formulation was also the most preferred by respondents due to its strong and fresh aroma, appealing color, and pleasant texture on the skin. All formulations had pH values within the safe range (5.5–7), did not cause skin irritation, and demonstrated stability during storage. In conclusion, pineapple peel extract is effective as a natural active ingredient in spray hand sanitizer formulations. This product not only exhibits strong antibacterial activity against E. coli but is also safe, stable, and presents an environmentally friendly alternative to support improved public hand hygiene.